A Customer Discovery Approach to Understanding Generation Z Housing Preferences in Urban Jakarta for an Architectural Startup - M. Faiz Amali; Wawan Dhewanto (Borong Newinera Publisher, 2026)
This study examines the housing preferences of Generation Z in Jakarta and explores how these preferences can inform the development of a viable business model for a proposed architectural startup. Rapid urbanization, rising housing costs, and changing lifestyles have led Generation Z to demonstrate housing needs that differ from conventional homeownership-oriented models. However, many architectural services in Indonesia have not fully adapted to these shifts. This research adopts a Customer Discovery approach based on Steve Blank’s framework, employing a sequential mixed-method design. Primary data were collected through a survey of 50 Generation Z respondents in Jakarta and followed by in-depth interviews with five potential users to test and refine the proposed service concept. The findings indicate that Generation Z prioritizes privacy, flexibility, transparent design processes, and optional social interaction within housing environments. Assumptions related to emotional loneliness as a dominant housing driver and fully digital architectural services were not empirically supported. The study results in a validated Business Model Canvas that positions architectural services as modular, transparent, and hybrid, combining digital accessibility with direct interaction. This research contributes to architectural entrepreneurship by demonstrating the applicability of Customer Discovery in developing service-based architectural business models aligned with generational needs.